Influência da via de parto sobre os resultados perinatais de mulheres que tiveram parto prematuro - Ribeiro, Gilberto Gomes (2009)
Objectives: to evaluate the influence of route of delivery on perinatal outcomes, in women who had preterm delivery; to evaluate demographic and obstetric characteristics as determinants of mode of delivery. Subjects and methods: it is a cross-sectional study from the charts of women who had preterm delivery, followed in the Service of Maternal-Fetal Medicine of Maternidade-Escola Assis Chateaubriand – Universidade Federal do Ceará. There were analyzed 195 pregnant women and 195 newborns coming from these singleton pregnancies, without clinical maternal, fetal and obstetric complications, presenting gestational age between 22 and 36 weeks and six days and fetal weight equal or above 500 grams. Demographic and obstetric characteristics and perinatal outcomes were evaluated in the general population and in each group (vaginal and abdominal delivery), being later compared with each other. For comparative statistical analysis among the two groups, it was utilized the Mann-Whitney test. The calculation of the reason of adjusted risk was accomplished through the software SAS version 9.1.3 and through Logistical and Multinomial Regression. All were considered statistically significant when p < 0.05. Results: the majority of pregnant women (81.5%) was admitted in active spontaneous preterm labor and 43.1% had premature rupture of the membranes. Tocolytic agents and corticosteroids were used, respectively, in 41.6% and 58.3% of women in false preterm labor and most of deliveries (74.4%) happened by vaginal route. At the moment of delivery, the average gestational age was 32.6 weeks. When the two groups were compared, false preterm delivery, premature rupture of the membranes and the administration of tocolytic drugs and corticosteroids increased, significantly, the risk of cesarean section (RRs 6.10, 1.64, 1.95 e 1.82, respectively), while the active preterm delivery decreased, significantly, this risk (RR 0.16, 95% CI - 0.11 a 0.25). The mean weight of the newborns was 1873g and they were classified as appropriate for gestational age in 76.7%. They needed for admission to the intensive care unit in 62.1% of cases, 21% required surfactant, 90.8% needed mechanic ventilation, 4.6% presented neonatal injury and the index of neonatal death was 8.7%. When the two groups were compared, the cesarean section significantly increased the chance of the Apgar score at 5° minute to be ≥ 7 (RR 1.06, 95% CI - 1.01 a 1.13). After logistic regression of COX adjusted for factors that could influence perinatal outcomes, had not been observed statistically significant differences between the two groups. Conclusions: it had not been found statistically significant differences in perinatal outcomes among newborns of vaginal delivery and cesarean section in women who had preterm delivery. Regarding obstetric characteristics, false preterm delivery, premature rupture of the membranes and the use of tocolytic agents and corticosteroids increased, significantly, the risk of cesarean section while the active preterm delivery decreased, significantly, this risk.